Diskrepansi Antara Objek Kewajiban Pelaporan Bagi Bank Berdasarkan Undang-Undang Pencucian Uang Dengan Yang Wajib Dirahasiakan Berdasarkan Ketentuan Anti-Tipping Off - Yanuar, Muh Afdal (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2023)
Based on anti-tipping off provisions, the object that must be kept confidential by the reporting party (inter alias, the Bank) is information related to Suspicious Transactions Report (STR). Meanwhile, things that become the object of reporting obligations for banks also include cash financial report (CTR), and international funds transfer instructions (IFTI). This paper will discuss the legal problems that arise and the paradigm that needs to be formed regarding the discrepancy between objects of reporting obligations for banks based on AML laws and objects that must be kept secret under anti-tipping off provisions. This paper was formed using normative research methods with conceptual, statutory, and comparative approaches. In this paper it is concluded that: (a) the legal problems that arise related to the issues discussed in this paper are that there are no specific provisions that expressively can be appointed if there is a disclosure of the fact related to CTR or IFTI; and (b) The paradigm that needs to be formed regarding the issues discussed in this paper is that Article 12 of the AML Law (anti-tipping off) is applied to violations of disclosing STR. Meanwhile, for the disclosure of CTR and IFTI, the provision that was applied was Article 11 of the AML Law.